Effects of the partial replacements of Oil Palm Boiler Clinker (OPBC) on the density and compressive strength of concrete - Muhammad Lutfi Othman; Noor Nabilah Binti Sarbini; Redzuan Abdullah; Mohamad Salleh Bin Yassin (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Oil Palm Boiler Clinker (OPBC) is a promising waste material that can be deployed toward sustainable development. Researchers have been looking into the potential of industrial waste and by-products to provide an alternative to natural stone aggregates in concrete production. This study aims to determine an OPBC concrete mix eligible for lightweight reinforced precast concrete products according to BS EN 13369:2013. Design/methodology/approach: The concrete mix design is determined via the trial mix method, where percentages of OPBC are varied as partial replacements in the control mix. Raw OPBC is collected from a local palm oil mill in Johor, Malaysia and is processed to be implemented in the concrete mix. Three 100mm cube samples of nine OPBC mixes and one control mix are tested and weighed on day 1, day 7, and day 28 to determine their cube compressive strength and density to BS EN 12390-3:2009. The mix that fulfils the requirements is the mix with 90% coarse clinker and 90% fine clinker, cured by the method of air curing, which achieved a cube compressive strength of 38.66N/mm2 and density of 1920kg/m3. Findings: In conclusion, the results show that OPBC concrete is a green alternative to standard concrete that does not differ significantly in terms of strength while offering a density reduction of as much as 16%. Originality/value: This paper is original Paper type: Research paper